Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12879-023-08516-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diagnostic delay of pulmonary tuberculosis among children and adolescents in Quzhou, China: results from the surveillance data 2011–2021

Yating Zhang,
Bingdong Zhan,
Xiaogang Hao
et al.

Abstract: Purpose Tuberculosis is a high-burden disease and a major health concern in China, especially among children and adolescents. The purpose of this study was to assess risk factors for diagnostic delay in students with pulmonary tuberculosis in Quzhou City in eastern China. Patients and methods Cases of PTB in students and relevant information in Quzhou from 2011 to 2021 were collected using the TB Management Information System. The outcome of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…We also found that the symptoms of pulmonary tuberculosis among students in suburb district were mild; the positive rate of pathogens was low, and it was difficult to detect and diagnose compared to the general population, with strong concealment. It is necessary to strengthen students' active physical examination screening and molecular biological detection technology, which is consistent with the fact that students' tuberculosis patients are easily found in Wuhan every year during graduation, admission, and annual physical examination and similar to many research results ( 19 – 23 ).…”
Section: Discussionsupporting
confidence: 56%
“…We also found that the symptoms of pulmonary tuberculosis among students in suburb district were mild; the positive rate of pathogens was low, and it was difficult to detect and diagnose compared to the general population, with strong concealment. It is necessary to strengthen students' active physical examination screening and molecular biological detection technology, which is consistent with the fact that students' tuberculosis patients are easily found in Wuhan every year during graduation, admission, and annual physical examination and similar to many research results ( 19 – 23 ).…”
Section: Discussionsupporting
confidence: 56%